Digital Entrepreneurship: Typography T-shirt Design Production in SMA Negeri 1 Percut Sei Tuan - Gustianingsih Gustianingsih; Nurhayati Harahap; Amhar Kudadiri; Emma Marsella (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this community service activity is to answer the problems at SMA Negeri 1 Percut Sei Tuan: the lack of interest in digital-based entrepreneurship, the lack of knowledge and skills of students in digital entrepreneurship practices so that students do not always lead to conventional entrepreneurship, limited capital in providing equipment, renting online platforms, and marketing costs, and the lack of commitment in understanding and implementing digital entrepreneurship, both from students and schools. This activity was carried out with three methods, namely equipment procurement, training, design assistance, and assistance in selling T-shirts at the market. The results of the activity include the availability of typography t-shirts with creative writings and then the t-shirts are marketed online in marketplaces, such as Shopee and Tokopedia. Currently, 50 t-shirts with typography designs have been marketed. The typography t-shirt design production development program at SMA Negeri 1 Percut Sei Tuan aims to enhance inclusive industries and encourage innovation through digital entrepreneurship training for students. The main priorities are the procurement of digital platforms, typography t-shirt production training, and the enhancement of digital entrepreneurship interest and knowledge in school.